Wind power integration : connection and system operational aspects. - Fox, Brendan; Flynn, Damian; Bryans, Leslie (IET Standards, 2014)
The book attempts to provide a solid grounding in all significant aspects of wind power integration for engineers in a variety of disciplines. Thus a mechanical engineer will learn sufficient electrical power engineering to understand wind farm voltage regulation and fault ride-through problems; while an electrical engineer will benefit from the treatment of wind turbine aerodynamics. They will both wish to understand electricity markets, and in particular how wind energy is likely to fare. The introductory chapter charts the remarkable growth of wind energy since 1990. The various technical options for wind power extraction are outlined. This chapter then goes on to describe the potential problems of large-scale wind integration, and outlines some possible solutions. The second chapter is essentially an electrical power engineering primer, which will enable non-electrical engineers to cope with the concepts presented in Chapters 3 and 4.-Chapter 3 deals with wind turbine generator technology, with particular attention being paid to current variable-speed designs. Chapter 4 is concerned with wind farm connection, and the implications for network design - an area lacking an established methodology to deal with variable generation. Chapter 5 addresses the key issue of power system operation in the presence of largely unpredictable wind power with limited scope for control. Energy storage provides a tempting solution; the treatment here concentrates on realistic, low-cost options and imaginative use of existing pumped storage plant. The importance of wind power forecasting is emphasised, and forms the main theme of Chapter 6. The encouraging progress in the last decade is described. Ensemble forecasting offers a useful operational tool, not least by providing the system operator with an indication of forecast reliability.-Finally, Chapter 7 summarises the main types of electricity market, and discusses the prospects for wind power trading. The main renewable energy support schemes are explained and discussed.
Previous edition: London: Institution of Electrical Engineers, 2007.
Keywords: Wind power.; elektronické knihy; electronic books